Crazy heart - Bridges, Jeff, 1949-; Gyllenhaal, Maggie, 1977-; Duvall, Robert; Twentieth Century-Fox Film Corporation ([United States] : 20th Century Fox, 2010)
The powerful story of a country music star's rocky road to redemption. Bad Blake is a boozy, broken-down singer who reaches for salvation with the help of Jean, a journalist who discovers the real man behind the music. But will Bad's hard-livin' ways and crazy heart cost him his last chance at a comeback?
Title from container.
Jeff Bridges, Maggie Gyllenhaal, Robert Duvall.
Rating: R; for language and brief sexuality.
Blu-ray disc, widescreen; requires Blu-ray player.
English dialogue; Spanish and French subtitles; English subtitles for the deaf and hard of hearing.
Keywords: Country musicians -- Drama; Man-woman relationships -- Drama; Alcoholics -- Drama; Feature films; Fiction films; Video recordings for the hearing impaired